Metabolic Syndrome: Updates on Pathophysiology and Management in 2021 - Fahed, Gracia; Aoun, Laurence; Bou Zerdan, Morgan; Allam, Sabine; Bou Zerdan, Maroun; Bouferraa, Youssef; Assi, Hazem I. (International journal of molecular sciences, 2022)
Metabolic syndrome (MetS) forms a cluster of metabolic dysregulations including insulin resistance, atherogenic dyslipidemia, central obesity, and hypertension. The pathogenesis of MetS encompasses multiple genetic and acquired entities that fall under the umbrella of insulin resistance and chronic low-grade inflammation. If left untreated, MetS is significantly associated with an increased risk of developing diabetes and cardiovascular diseases (CVDs). Given that CVDs constitute by far the leading cause of morbidity and mortality worldwide, it has become essential to investigate the role played by MetS in this context to reduce the heavy burden of the disease. As such, and while MetS relatively constitutes a novel clinical entity, the extent of research about the disease has been exponentially growing in the past few decades. However, many aspects of this clinical entity are still not completely understood, and many questions remain unanswered to date. In this review, we provide a historical background and highlight the epidemiology of MetS. We also discuss the current and latest knowledge about the histopathology and pathophysiology of the disease. Finally, we summarize the most recent updates about the management and the prevention of this clinical syndrome.